Thermal inactivation spectrum of influenza A H5N1 virus in raw milk - Mohammed Nooruzzaman; Lina M. Covaleda; Pablo Sebastian Britto de Oliveira; Nicole H. Martin; Katherine J. Koebel; Renata Ivanek; Samuel D. Alcaine; Diego G. Diel (Nature Communications)
Abstract The spillover of highly pathogenic avian influenza (HPAI) H5N1 virus to dairy cows and shedding of high amounts of infectious virus in milk raised public health concerns. Here, we evaluated the decay and thermal stability spectrum of HPAI H5N1 virus in raw milk. For the decay studies, HPAI H5N1 positive raw milk was incubated at different temperatures and viral titers and the decimal reduction time values (D-values) were estimated. We then heat-treated HPAI H5N1 virus positive milk using different thermal conditions including pasteurization and thermization conditions. Efficient inactivation of the virus (5-6 logs) was observed in all tested conditions, except for thermization at 50 °C for 10 min. Utilizing a submerged coil system with temperature ramp up times that resemble commercial pasteurizers, we showed that the virus was rapidly inactivated by pasteurization and most thermization conditions. These results provide important insights into the efficacy of thermal conditions and food safety measures utilized in the dairy industry.